Nurses' attitude toward patients' safety climate during COVID-19 pandemic: a cross-sectional study† - Nassehi Asra; Ghorbanzadeh Kobra; Moayedi Somaye; Jafari Javad; Mahmoodi Parvin; Jafari Mojtaba (Sciendo, 2024)
Patient safety is a fundamental factor in improving the quality of care provided in hospitals. Therefore, it is considered a significant parameter by all healthcare organizations around the world. The present study was conducted to investigate the attitude of nurses toward the patient safety climate during the Coronavirus Disease 2019 (COVID-19) pandemic in the southeast of Iran.